Business ethics : - Ferrell, O. C (McGraw Hill, 2017)
PART: 1 AN OVERVIEW OF BUSINESS ETHICS ; PART 2: ETHICAL ISSUES AND THE INSTITUTIONALIZATION OF BUSINESS ETHICS ; PART 3: THE DECISIONMAKING PROCESS ..,